Planificación turística como proceso de certificación sostenible de la playa San Lorenzo, cantón Manta, Manabí - Ávalos Zambrano, Mayda Karola (2019)
The purpose of the research was to develop a strategic development plan that aims to achieve the certification of good tourism sustainability practices at San Lorenzo beach, Manta. This work was of a mixed type with a descriptive approach, for which several methodologies related to sustainable development had to be analyzed, among them the Inter-American Institute for Cooperation on Agriculture (2014), Garduño (2009), Ten (2011) and Sonaglio and Da Silva (2009). In addition, to the use of the criteria established for the tourist certification of beaches endorsed by the Ecuadorian Institute of Normalization INEN (2018), for the development of this proposal. Therefore, four research phases were defined, beginning with the multidimensional evaluation of the territory through the application of information collection cards, the current status of the tourism offer in the study area was determined, together with the evaluation of the demand through Surveys related to the consumption of tourism services in spaces destined to the conservation of natural heritage, guidelines were defined to establish the foundations of the development plan, a zoning study was developed that allows geospatial distribution in an efficient and sustainable way in the long term and that allowed to define the key points for the creation of strategic planning. Emphasizing that the zoning could determine the need to establish three areas for environmental recovery, public use and sustainable use. As a result of the Strategic Plan, the need to implement three projects aimed at the administrative, touristic and environmental management of the study area was determined; the implementation of Tourist Signaling and Facilities and Continuous Technical Instruction.